2022
DOI: 10.21608/jpp.2022.154932.1152
|View full text |Cite
|
Sign up to set email alerts
|

Rationalization of Water Use and Fertilization of Globe Artichoke Using Magnetic Water Irrigation

Abstract: Two field experiments were carried out during the two growing seasons of 2019/2020 and 2020/2021 at the El Kanater Hort. Res. Station, El Kaloubia governorate Egypt, to study the effect of irrigation with normal water, magnetized water at 100, 75% of potential evapotranspiration, under different levels of N, P and K of the recommended doses fertilization and their combined interactions on productivity and water use efficiency of globe artichoke. The experiment design was a split plot with three replicates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
3
2
0
Order By: Relevance
“…magnetic water revealed the highest levels of water productivity in comparison to the other treatments. These findings are consistent with those of Ismail et al (2022), where showed that globe artichokes irrigated with 75 or 100% ETc. magnetic water during drought stress generated the highest efficiency of water use.…”
Section: Water Productivity (Wp) Kgm -3supporting
confidence: 92%
See 3 more Smart Citations
“…magnetic water revealed the highest levels of water productivity in comparison to the other treatments. These findings are consistent with those of Ismail et al (2022), where showed that globe artichokes irrigated with 75 or 100% ETc. magnetic water during drought stress generated the highest efficiency of water use.…”
Section: Water Productivity (Wp) Kgm -3supporting
confidence: 92%
“…Additionally, magnetic water might stimulate the production of proteins, rates of photosynthesis, and pigments considerably which could contribute to an increase in garlic yield (Mostafa 2020). Similar results were obtained by Ismail et al (2022), that noticed a significant increase in artichoke yield ton/fed when they used magnetic water to irrigate the plants at either 75 or 100% ETc. Moreover, As stated by Faridvand et al (2021), applying magnetic water treatment substantially improved the yield of fennel seeds.…”
Section: Production Per Faddensupporting
confidence: 67%
See 2 more Smart Citations
“…However, hot pepper is particularly vulnerable to drought stress due to its wide range of transpiring leaf surfaces and high stomatal conductance, as well as its shallow root system (Zayzay Jr, 2015;Agliassa et al, 2021). To ensure high yields and su cient water supply, moist soil is required throughout the growing season (Ismail and Ozawa, 2009;Agliassa et al, 2021). Hot pepper cultivation is prevalent in warm and semi-arid countries, including Ethiopia, where it is a high-value cash crop used in many ways (Dorji et al, 2005; Adametie and Mitku, 2021).…”
Section: Introductionmentioning
confidence: 99%